HUBUNGAN ANTARA TRUSTWORTHINESS DENGAN INTENSI TURNOVER PADA AGEN ASURANSI JIWA BERSAMA BUMIPUTERA SURABAYA - Jati, Suci Damar (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Â The aim of this study was to determine the trustworthiness of therelationship between turnover intention. The population of this research is the agent AJB Bumiputera Satellite Darmo Surabaya branch, Wonocolo, and Wonokromo. Subjects of this study (N = 90) were taken from the population by using accidental sampling technique. Data collection using the questionnaire enclosed with 5 scale questionnaire answers and open. Data were tested using non-parametric correlation techniques, namely Spearman. From this research, found a negative correlation between turnover intention trustworthiness with AJB Bumiputera agents Satellite Darmo Surabaya branch, Wonocolo, and Wonokromo (r = -0.396; p = 0.000). Another factor which affects of crossÂ  tabulation known factors associated with turnover intention is the last age and education. In this study suggested that the supervisor can perform a self-evaluation related to forming ability, benevolence, and integrity of trust in the agent.